Influences of minerals transformation on the reactivity of high temperature char gasification - Bai, J.; Li, W.; Li, Chun-Zhu; Bai, Z.; Li, B. (Elsevier, 2010)
Two Chinese coals were used in this study and coal chars were prepared at different temperatures. High temperature gasification of coal chars with CO2 was investigated in a bench scale fixed-bed reactor and the transformations of minerals from these two coals were also studied from 1100 to 1500 °C. Mineral matters produced at different temperature and ash generated after gasification were collected and analyzed by XRD and FTIR. It was found that the iron oxides were only catalytic mineral matters existing at high temperature. And gasification behaviors above ash melting temperature were different for different mineral composition, especially the content and form of iron oxide, which not only accelerates the gasification reaction, but also reduces the influence caused by melting minerals. Crown Copyright © 2009.